Open and Distance Learning: A Catalyst for Women Empowerment - Uthman, Ganiyat Adejoke Adesina; Olusanya, Samuel Olumuyiwa; Ohioze, Wilson Friday (West African Journal of Open and Flexible Learning, 2015)
Open and distance learning education has come of age in Nigeria. For over a decade, the National Open University of Nigeria (NOUN) still remains the only one-mode university in Nigeria. Education is the bedrock of women empowerment, be it formal or informal. Women empowerment is an avenue for the development of mental and physical capacity, power or skills in women for them to operate meaningfully in their social milieu, thereby experiencing a more favourable level of social recognition and subsequently enhance their economic status. The objectives of this paper is to examine whether open and distance learning has an influence on women empowerment in Nigeria and to also ascertain if the cost of undergoing ODL in Nigeria is affordable for Nigerian women that enrolled with NOUN. The paper made use of primary data of questionnaire analysis and chi-square statistical analysis was used as the estimation techniques. The findings showed that Open and Distance Learning has significant effects on Women empowerment in Nigeria and that the cost of undergoing ODL in Nigeria is not affordable for Nigerian Women that enrolled with NOUN. Conclusively, it is recommended that women should be encouraged to undergo relevant ODL programmes that are designed to meet their needs. The cost of undergoing ODL should be reduced to encourage more women enrollment for the programmes.